2013
DOI: 10.1007/s00590-013-1187-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of osteoporotic vertebral compression fractures with percutaneous kyphoplasty: a report of 196 cases

Abstract: The incidence of osteoporotic vertebral compression fracture (OVCF) is increased recently. Percutaneous kyphoplasty (PKP) has recently been shown to have a curative effect on OVCF. Unfortunately, related complications arising from PKP cannot be ignored, such as cement leaks, fever, and intercostal neuralgia. This study aimed to investigate the common complications of PKP in the treatment of OVCF patients and analyze the causes and assess prevention and control measures. A total of 196 patients (204 vertebrae) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The increasing elderly population throughout the globe has brought increasing attention to osteoporosis, the most important cause osteoporotic vertebral compression fractures (OVCF). 1 , 2 OVCF has a prevalence of more than 30% in the population older than 65 years. 3 OVCF is associated with acute and chronic pain, progressive spinal deformity, a decreased quality of life, impaired physical function and increasing mortality.…”
mentioning
confidence: 99%
“…The increasing elderly population throughout the globe has brought increasing attention to osteoporosis, the most important cause osteoporotic vertebral compression fractures (OVCF). 1 , 2 OVCF has a prevalence of more than 30% in the population older than 65 years. 3 OVCF is associated with acute and chronic pain, progressive spinal deformity, a decreased quality of life, impaired physical function and increasing mortality.…”
mentioning
confidence: 99%
“…When left untreated, many patients may suffer significant disability secondary to deformities, which may lead to thromboembolic complications [13]. For management of such fractures, percutaneous Vertebroplasty and Kyphoplasty are the most used surgery, with significantly good outcomes in controlling pain and disability [4,[14][15][16]. However, with increased number of cases receiving vertebroplasty and kyphoplasty, and with longer follow up available, many complications showed up as a specific complication to this category of surgery, including cement leakage, re-collapse of the operated vertebra, with an incidence reaching 38.9% [17], and refracture of the operated vertebra or the adjacent ones which has a reported incidence of 5% [18].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used operation is PKP, which has achieved satisfactory outcomes evaluated by VAS, ODI, and local CA at each follow-up visit compared with those at preoperative admission ( p < 0.05) [ 14 ]. However, with the accumulation of clinical cases and prolonged follow-up period, some disadvantages were documented including cement leakage, recollapse, infection, and even refracture [ 15 , 16 ]. Wei et al reported that 1 (5%) patient had an adjacent vertebral fracture after PKP [ 17 ], and Wang et al found that 79 (38.9%) patients who were treated with PKP had recollapse during followed up visits [ 18 ].…”
Section: Discussionmentioning
confidence: 99%